Editorial (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
Editor Folake Ruth Aluko University of Pretoria, South Africa  Associate Editor Oyeyemi Ololade Aitokuhehi University of Lagos, Nigeria